An Evaluation of the Interaction of Lysine and Methionine in Diets for Growing Broilers - Si, Jianlin; Kersey, J.H.; Fritts, C.A.; Waldroup, P.W. (International Journal of Poultry Science, 2003)
Levels of lysine (Lys) and methionine (Met) in excess of NRC recommendations may result in enhanced performance, especially in regard to breast meat yield (BMY). Some people have interpreted the "ideal Protein" concept to suggest that amino acids such as Met should be kept in an "Ideal" ratio with Lys even though Lys may be in excess of actual needs. The objectives of this study were twofold: 1) to evaluate the effects of levels of Lys and Met in excess of NRC recommendations in diets of male broilers grown for further processing; 2) to determine if any interaction exists between levels of Lys and Met when minimum levels are exceeded. Three studies of identical design were conducted. Corn, soybean meal and corn gluten meal of known composition were used to formulate basal diets for 0 to 3, 3 to 6, and 6 to 9 wk which provided a minimum of 110% of NRC (1994) amino acid recommendations other than Lys, Met and TSAA which were at 100% of recommended levels. From the base diets, experimental diets were derived by additions of lysine HCl and DL methionine to provide a factorial arrangement with three levels of Lys (NRC, NRC + 0.15%, NRC + 0.3%) and four levels of Met and TSAA (NRC, NRC + 0.05%, NRC + 0.1%, NRC + 0.15%). Each of the 12 diets was fed to two (trial 1) or four (trial 2 and 3) replicate pens of 50 male broilers (Cobb 500). Birds were weighed and feed consumption determined at 3, 6, 7, 8, and 9 week. Samples of birds were processed at 7, 8, 9 wk for parts yield. Although significant differences in performance were noted among trials due to environmental temperature there was no trial x treatment interaction so data were combined. There were no significant interactions between Lys and Met for any parameter when both were fed equal to or in excess of NRC recommendations. Increasing Lys above NRC recommendations significantly improved BW and FCR at 21 d but not at later ages; BMY was improved by increasing Lys only at 63 d. Increasing Met above NRC significantly improved FCR at 42 and 56d; there was no significant effect of Met levels on BMY at any age. Results of this study suggest that people formulating diet on "Ideal Protein" basis should not elevate the level of Met if lysine is in excess of its minimum needs.